Imagine There Is No Plegia. Mental Motor Imagery Difficulties in Patients with Traumatic Spinal Cord Injury - Thomschewski, Aljoscha; Ströhlein, Anja; Langthaler, Patrick B.; Schmid, Elisabeth; Potthoff, Jonas; Höller, Peter; Leis, Stefan; Trinka, Eugen; Höller, Yvonne (Frontiers in Neuroscience, 2017)
In rehabilitation of patients with spinal cord injury (SCI), imagination of movement is a candidate tool to promote long-term recovery or to control futuristic neuroprostheses. However, little is known about the ability of patients with spinal cord injury to perform this task. It is likely that without the ability to effectively perform the movement, the imagination of movement is also problematic. We therefore examined, whether patients with SCI experience increased difficulties in motor imagery (MI) compared to healthy controls. We examined 7 male patients with traumatic spinal cord injury (aged 23-70 years, median 53) and 20 healthy controls (aged 21-54 years, median 30). All patients had incomplete SCI, with AIS (ASIA Impairment Scale) grades of C or D. All had cervical lesions, except one who had a thoracic injury level. Duration after injury ranged from 3 to 214 months. We performed the Movement Imagery Questionnaire Revised as well as the Beck Depression Inventory in all participants. The self-assessed ability of patients to visually imagine movements ranged from 7 to 36 (Md=30) and tended to be decreased in comparison to healthy controls (ranged 16-49, Md=42.5; W=326.5, p=0.055). Also, the self-assessed ability of patients to kinesthetically imagine movements (range=7-35, Md=31) differed significantly from the control group (range=23-49, Md=41; W=337.5, p=0.0047). Two patients yielded tendencies for depressive mood and they also reported most problems with movement imagination. Statistical analysis however did not confirm a general relationship between depressive mood and increased difficulty in MI across both groups. Patients with spinal cord injury seem to experience difficulties in imagining movements compared to healthy controls. This result might not only have implications for training and rehabilitation programs, but also for applications like brain-computer interfaces used to control neuroprostheses, which are often based on the brain signals exhibited during the imagination of movements.